Optimum Financing Portofolio of islamic Microfinance Institutions: Indonesia Case - Imron Mawardi (Universidad del Zulia -Venezuela, 2019)
The purpose of this paper is to analyze the risk-return of financing and find the optimum financing instruments portfolio of Islamic microfinance institutions (IMFI).The optimum portfolio financing is determined by the minimum coefficients of variation of financing instruments portfolio, namely Murabahah, Mudharabah-Musyarakah, and Ijarah. The methodology of this study is quantitative, which is using risk and return theory to compute risk, return, variance, and coefficient of variation of financing instruments portfolio. The solver program of Microsoft Excel is used to find the optimum combination and composition of financing portfolio. This research found that ijarah financing has the highest return.